2023
DOI: 10.1109/access.2023.3236084
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Artificial Intelligence in Future Rehabilitation Services: A Systematic Literature Review

Abstract: Artificial intelligence technologies are considered crucial in supporting a decentralized model of care in which therapeutic interventions are provided from a distance. In the last years, various approaches have been proposed to support remote monitoring and smart assistance in rehabilitation services. A comprehensive state-of-the-art of machine learning methods and applications is presented in this review. Following PRISMA guidelines, a systematic literature search strategy was led in PubMed, Scopus, and IEEE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Additionally, our research team has continued to delve into PSS approaches in healthcare that exploit AI. Our findings have shown that there is research being done in the filed of AI in rehabilitation (Davenport and Kalakota, 2019;Neuhüttler et al, 2020;Preidel and Stark, 2021;Aranda-Muñoz et al, 2022;Mennella et al, 2023) and AI in prosthetics and orthotics (Mai and Commuri, 2013;Kidziński et al, 2019;Nayak and Kumar Das, 2020;. To date, no explicit PSS literature (with or without the use of AI) concerning amputee aftercare, their evolving needs or the manufacture, distribution, ownership and use of prosthetics has been found.…”
Section: State Of the Art Product Service Systems For Amputee Healthcarementioning
confidence: 66%
“…Additionally, our research team has continued to delve into PSS approaches in healthcare that exploit AI. Our findings have shown that there is research being done in the filed of AI in rehabilitation (Davenport and Kalakota, 2019;Neuhüttler et al, 2020;Preidel and Stark, 2021;Aranda-Muñoz et al, 2022;Mennella et al, 2023) and AI in prosthetics and orthotics (Mai and Commuri, 2013;Kidziński et al, 2019;Nayak and Kumar Das, 2020;. To date, no explicit PSS literature (with or without the use of AI) concerning amputee aftercare, their evolving needs or the manufacture, distribution, ownership and use of prosthetics has been found.…”
Section: State Of the Art Product Service Systems For Amputee Healthcarementioning
confidence: 66%
“…However, applications of AI are still relatively new and AI is not yet routinely used in clinical decision-making. Few of these systems have been evaluated in clinical studies [23] .…”
Section: The Impact Of Ai In Healthcarementioning
confidence: 99%
“…Due to remarkable technological advancements, AI has ushered in innovative applications within the realm of care assistive [23] . Significant progress was made in wearable devices capable of measuring physiological changes and facilitating real-time patient monitoring [47] .…”
Section: The Impact Of Ai In Healthcarementioning
confidence: 99%
“…Several studies discuss the potential of AI in rehabilitation, including its use in assisting rehabilitation sessions, evaluating treatment progress, and providing prognosis regarding the risk of complications or treatment success. These advancements in AI have the potential to improve decision-making, develop precision medicine tools, and optimize rehabilitation programs [4][5][6]. Determining the rehabilitative protocol to use, depending on the patient's medical history and clinical features, is a fundamental purpose.…”
Section: Introductionmentioning
confidence: 99%